Magnitude and its associated factors of gestational trophoblastic disease in East African countries, systematic review and meta-analysis - Abebaw, Nigusie; Biset, Gebeyaw; Yimer, Nega; Gezie, Hailemariyam; Workneh, Moges; Mulugeta, Chalie; Emagneneh, Tadele; Alamrew, Abebaw; Birhan, Zelalem (Frontiers in Oncology, 2025)
BackgroundThe term of gestational trophoblastic disease (GTD) is used to describe a group of tumors that are characterized by abnormal trophoblastic proliferation. Histologically, GTD includes the pre-malignant partial hydatidiform mole, complete hydatidiform mole, and malignant invasive moles that are choriocarcinoma, placental site trophoblastic tumors, and epithelioid trophoblastic tumors.Method and materialThe protocol for this review was registered on PROSPERO, accessible at CRD42024560408. We used the “PRISMA 2020 Statement: An Updated Guideline for Reporting Systematic Reviews and Meta–analysis. All original and published cross-sectional, cohort, and case-control types of studies were reported during the study period. Studies conducted in both community and institutional settings were considered. Two reviewers independently assessed the risk of bias in the included studies using tools developed by the Joanna Briggs Institute, which comprise eight criteria.ResultData was systematically searched by Google Scholar (n = 214), HINARI (n = 46), Scopus (n = 40), and PubMed (n = 146) on 1 May 2024. A total of 13 studies from five countries in East Africa have been included. The random effects model showed that the prevalence of GTD among pregnant women was 22% (95% CI: 10%–33%). Women who are aged between 30 and 39 years (AOR = 0.11, 95% CI: 0.05–0.16), women who have a previous history of GTD (AOR = 0.24, 95% CI: 0.00–0.47), women who have a previous complication of the reproductive organ system (AOR = 0.23, 95% CI: 0.10–0.35), and women who have more than two histories of pregnancy (AOR = 0.9, 95% CI: 0.06–0.11) were significantly associated with the outcome variable.ConclusionThis finding revealed that the pooled prevalence of GTD among pregnant women was high. Women who are aged between 30 and 39 years, have a previous history of GTD, and women who have had previous complications during pregnancy, and women who have more than two histories of pregnancy were significantly associated with the outcome variable.